Pesticide usage practices and the exposure risk to pollinators: A case study in the North China Plain - Hongyu Mu; Kai Wang; Xiaomei Yang; Wen Xu; Xuejun Liu; Coen J. Ritsema; Violette Geissen (Ecotoxicology and Environmental Safety, 2022)
Due to the frequent pesticide applications, bees are suffered from pesticide exposure risks via consumption and direct contact with sprayed drifts. However, if pesticides are misused and the potential exposure risk to bees based on realistic pesticide application data are still little reported. In this study, pesticide application patterns in wheat-maize rotation system, vegetable and apple producing areas, was studied by interviewing farmers in Quzhou County, the North China Plain. The pesticide use status was evaluated by the recommended and actual applied dose and risk quotient (RQ) based Bee-REX model was used to assess the exposure risks of pesticide to bees based on the collected pesticide application data. The results showed that over half (52 %) of farmers in selected sites misused pesticides and orchard owners were frequently misused pesticides. Positive correlations were found between pesticide usage performance and farmers’ specialized training experience. Pesticides applied in orchards have caused higher exposure risks to bees with the mean of RQs exceed 120 and 1880 via acute contact and dietary routes, respectively. Pesticide misuse significantly elevates the exposure risk to bees that the mean RQ under misuse scenarios was 5.8 times than that of correct use. Abamectin, fipronil and neonicotinoids contributed most to the pesticide exposure risk to bees. The main findings of this study imply that more sustainable pest and pollinator management strategies, including the moratorium high-risk insecticides and providing diverse flower resources and habitats, are highly needed. Additionally, measures such as implementing farmer educating and training programs should also be put on the agenda.